The Effectiveness of the Acceleration of the Irrigation Water Use Improvement Program (P3-TGAI) in the Covid-19 Pandemic in the South OKU District - Setiawan, Andi; Sari, Yunita; Sari, Fifian Permata (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2022)
The Acceleration of the Irrigation Water Use Improvement Program (P3-TGAI) is a program to meet irrigation water needs which is an extension of the program for the acceleration of improvement in irrigation water use, which is the rehabilitation, improvement, or construction of an irrigation network based on the participation of the farming community which is carried out by the Water User Farmers Association, the Association of Farmers Users of Water. Water or Parent Water User Farmers Association in a self-managed way. The purpose of this study was to determine and analyze the effectiveness of P3-TGAI during the Covid 19 pandemic in South OKU District. The theory used in the research is the theory of effectiveness. Effectiveness can be defined as the level of an institution's ability to achieve predetermined goals or objectives. The analytical method used is the descriptive quantitative analysis method. to measure the effectiveness of P3-TGAI using four indicators, namely program success, target success, program satisfaction, input and output levels, and overall goal achievement. The results of this study indicate that the overall effectiveness of P3-TGAI during the Covid 19 pandemic in the South OKU District has been successful and is categorized as effective. Of the five dimensions of effectiveness analyzed, two dimensions of effectiveness have not been implemented properly, namely the dimensions of program success and the dimensions of target success, while the dimensions of effectiveness that have been well implemented are the dimensions of satisfaction with the program, dimensions of input and output levels, and dimensions of overall goal achievement